Audit Problems of Waqf Institutions in Indonesia - Irwansah; M. Idris; Ardinata, Riki (SMART Insight, 2024)
The management of waqf in Indonesia faces serious challenges in terms of governance and accountability, especially related to the audit function of waqf institutions. Effective audits are the main prerequisites in ensuring transparency, professionalism, and sustainability of waqf asset management. This study aims to identify and prioritize the main problems of auditing in waqf institutions in Indonesia based on the views of experts. The method used is Delphi, involving 15 expert respondents consisting of academics, practitioners, and regulators in the field of waqf and Islamic economics. Data analysis was carried out using three main consensus indicators, namely mean value, standard deviation, and interquartile range (IR). The results of the study showed that all variables of waqf audit problems reached a consensus level (convergent). The three main priorities for waqf audit issues in Indonesia are financial transparency, management professionalism, and service quality. These findings affirm the importance of strengthening the audit system and waqf governance to increase public trust and the effectiveness of waqf management in Indonesia.